Writing Between Cultures - Godard, Barbara (TTR)

(untitled) (Association canadienne de traductologie, 1997)
AbstractWriting Between Cultures — This essay examines the traffic in languages or systematic interferences, the tropes of translation whereby the network of the Canadian literary system is produced. It focuses on two moments in that process, one whereby Canadian literatures are produced as Europe's other by vertical translation of Canadian concepts into classical languages and an erasure of horizontal translation among Amerindian languages as manifest in the writing of colonization, especially in the work of Marie de l'Incarnation. The second is the contemporary period where the theatre of cultures of Amerindian playwrights, Daniel David Moses in particular, restages the trope of non-translation to expose therein the rhetorical violence of imperialism and offers in its place a model of horizontal translation between Amerindian languages. Performance as repetition with a difference or rewriting is another mode of translation, characterized by a theory of language as event not as mimesis.